Comprehensive multisite efficiency equation for semiconductor test equipment - Khoo, V. Ching (Taylor's University, 2020)
Multisite efficiency (MSE) determines the effectiveness of improving multisite testing throughput, which ultimately affects the cost of tests. As indicated by International Technology Roadmap for Semiconductors 2.0 2015 Edition a decrease of the MSE relative to the test site increment has a negative effect on the testing throughput improvement. However, calculating the MSE accurately needs to consider all related variables such as test time, unit indexing time, tray exchange sequence time, testing yield, jam rate, and production capacity. The MSE equations identified from the previous literature are inaccurate and do not reflect the actual MSE situation. This study develops an equation which incorporates all the relevant variables for better prediction of testing throughput and the cost of test.